US Foreign Policy and the Rogue State Doctrine. - Miles, Alex (Routledge studies in US foreign policy., 2012)
Concerns over Iran's nuclear programme, North Korea's nuclear brinkmanship and, in the past, Iraq's apparent pursuit of WMD have captured the world's attention, and dominated the agenda of the American foreign policy establishment. But, what led policymakers and the US military to emphasise the threat of rogue states at the end of the Cold War? Going behind the vivid language of the 'axis of evil' and portrayals of undeterrable and reckless rogue states, this work demonstrates how the rogue state doctrine satisfied both domestic and international goals in the Clinton and Georg.